Operations for entrepreneurs: Can Operations Management make a difference in entrepreneurial theory and practice?. Issue 12 (2nd October 2022) - Fine, Charles H.; Padurean, Loredana; Naumov, Sergey
Abstract: Although entrepreneurship‐related papers have had some representation in Production and Operations Management (POM) over the past 30 years, the topic still seems a bit like a poor stepchild in the research of operations management (OM) scholars. Yet, entrepreneurship is important to the economy, and many schools are growing significantly their entrepreneurship programs and offerings but often without reference to or inclusion of operations courses. This paper is motivated by the question of the operations needs of new ventures and how they might differ from the needs of large, established firms. Toward that end, we review briefly the state of entrepreneurship scholarship in POM (and beyond), present our own (field‐based) research (and cases), and propose a framework for what we call "operations for entrepreneurs, " that we hope can be a basis for further productive research and curriculum development by the OM community.